IMPLEMENTASI STANDAR ISI DALAM KURIKULUM 2013 DI SEKOLAH DASAR - Ndaru Mukti Oktaviani; Isnaini Wulandari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The purpose of this study is 1) describe the problems in the implementation of content standards in the Curriculum 2013, 2) describe the factors that cause problems in the implementation of the Curriculum 2013 content standards in elementary schools.The research method used is case study. The study was conducted at Kuningan Regency, SDN Dukuhdalem, Japara District, SDN 1 Manislor, Jalaksana District, and SDN 1 Purwawinangun, Kuningan District. There are two types of research instruments used, observation sheets and interview guides. Qualitative data analysis is carried out interactively and takes place continuously at each stage of the study so that it is complete, and the data is saturated. The results of the study note that 1)  scope of the material on the spiritual attitude competence faces obstacles in terms of time, 2) scope of the material on social attitude competencies faces obstacles in terms of time, 3) scope of the material on the competency of outreach faces obstacles in terms of cost, 4) scope of the material on knowledge competence faces obstacles in terms of monotonous material, the extent of the material which is considered to be lacking. These four problems require seriousness in handling so that in the future the objectives of the curriculum 2013 can be achieved